Storying violence : unravelling colonial narratives In the Stanley trial - Starblanket, Gina; Hunt, Dallas (Arbeiter Ring Publishing, 2020)
In August of 2016, Cree youth Colten Boushie was shot dead by Saskatchewan farmer Gerald Stanley. Using colonial and socio-political narratives that underlie white rural settler life, the authors position the death of Boushie and trial of Stanley in relation to Indigenous histories and experiences in Saskatchewan. They point to the Stanley case as just one instance of Indigenous peoples' presence being seen as a threat to settler colonial security, then used to sanction the exclusion, violent treatment, and death of Indigenous peoples and communities.
Keywords: Stanley, Gerald -- (Farmer) -- Trials, litigation, etc.; Boushie, Colten.; Trials (Murder) -- Saskatchewan.; Trials (Manslaughter) -- Saskatchewan.; Indigenous peoples -- Violence against -- Saskatchewan.; Saskatchewan -- Race relations.; Saskatchewan -- Ethnic relations.; Procès (Meurtre) -- Saskatchewan.; Procès (Homicide involontaire) -- Saskatchewan.; Ethnic relations; Indigenous peoples -- Violence against; Race relations; Trials (Manslaughter); Trials (Murder); Saskatchewan; Trials, litigation, etc.